The Relationship between Online Game Addiction and Verbal Bullying in Adolescents at a Junior High School in Makassar - Iskandar Zulkarnaen; Esse Puji Pawenrusi; Andi Ayumar; Riona Fransina Bairsady (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Online gaming addiction is the habit of playing games excessively, exceeding 3-4 hours per day. Meanwhile, verbal bullying is a form of bullying carried out through words such as nicknames, reproaches, and cruel criticism. According to WHO (2020), the prevalence of verbal bullying in Indonesia reached 37% in girls and 42% in boys. The purpose of this study aims to determine the relationship between online game addiction and verbal bullying in adolescents at Advent Makassar Junior High School. The method of this study used a quantitative approach with a cross-sectional design. The number of respondents was 69 students who were taken through total sampling technique. The research instrument is a questionnaire that has been validated and used to measure the level of online game addiction and the intensity of verbal bullying. The results showed that of the 50 respondents who experienced online game addiction, 41 students (82.0%) had a high level of verbal bullying, and 9 students (18.0%) had a low level. While of the 19 respondents who were not addicted, 7 students (36.8%) experienced high verbal bullying and 12 students (63.2%) at a low level. The chi-square test results show a p value = 0.001 (p < 0.05), which means there is a significant relationship between online game addiction and verbal bullying. The conclusion is that there is a significant relationship between online game addiction and verbal bullying behavior among adolescents at Advent Junior High School Makassar.